Multifactorial Prediction of Anthracycline-Induced Cardiotoxicity in Childhood Cancer: 10 Years of Active Surveillance and Pharmacogenomics Studies at the Canadian Pharmacogenomics Network for Drug Safety - Aminkeng, Folefac (ELSEVIER SCIENCE INC, 2022)
10.1016/j.vascn.2017.09.005